Verifiably secure fast group authentication protocol with anonymous traceability for Internet of vehicles - Haibo ZHANG; Hongwu HUANG; Kaijian LIU; Xiaofan HE (Tongxin xuebao)
Identity authentication is the first line of defense for vehicles to access IoV (Internet of vehicles).However, the existing schemes cannot meet the requirements of efficient authentication of IoV well, nor can they realize fast anonymous traceability.In view of this, a bidirectional anonymous traceability group authentication protocol was proposed in IoV.In this protocol, a number of RSU (road side unit) were grouped quickly and dynamically.And the vehicles entering the RSU group were authenticated with the one-way trap gating property and semi-group property of Chebyshev chaotic map.When the vehicle switched between the RSU within a group, the reverse hash chain was used for fast handover authentication.In addition, the RSU within a group can trace anonymously and revoke the identity of malicious vehicles quickly by using blockchain, and can also freely change the ID of users who reveal their real identity.At the same time, the semantic security of the proposed protocol is proved by using the random predictor model.Finally, simulation results show the proposed scheme has good security and effectiveness.